Ultra-dense networks for 5G and beyond : modelling, analysis, and applications - Duong, Trung Q.; Chu, Xiaoli; Suraweera, Himal A. (John Wiley & Sons, Inc., 2019)
"A comprehensive insight into the theory, models and techniques of ultra-dense networks and applications in 5G and other emerging wireless networks -Ultra-dense networks and communications systems are emerging topics, having many applications that have potential to solve varieties of real-life problems -Presents recent advances in ultra-dense networks for 5G networks and beyond, i.e., cognitive radio networks, massive MIMO, device-to-device communications, mm-wave communications, and energy harvesting communications -One of the first books to focus solely on ultra-dense networks for 5G in a complete presentation Market description: Primary: postgraduate students, researchers and engineers in the field of wireless communications who will find it an ideal reference to further explore the potential of ultra-dense networks with a view to designing high speed communications in advanced networks of the future Secondary: researchers in academia, industry, as well as practitioners in governmental agencies"--